Neuromuscular control in chronic ankle instability, copers and healthy subjects during dynamic discrete tasks: A systematic review and meta-analysis. - Mohamadi, Somayeh; Rahmani, Nahid; Boozari, Sahar; Mohseni-Bandpei, Mohammad Ali; bidhendi-Yarandi, Razieh (Journal of Bodywork & Movement Therapies, 2026)
Chronic ankle instability (CAI) is one of the most prevalent lower limb injuries. The purpose of the present study was to systematically review and meta-analysis all related studies that investigated neuromuscular control in CAI individuals compare with copers and healthy subjects during dynamic discrete tasks. Available databases like PubMed, Scopus, Science Direct, Medline and Web of science were searched using related keywords from the beginning until the March 2024. Ten relevant articles met the inclusion criteria. The random effect model was used for the estimation of the pooled Standardized Mean difference (SMD) of outcomes in CAI compared with coper and healthy groups. Ten studies including the SEBT, jump landing, side cutting and Biodex balance dynamic task were included. Most of the studies considered in the present review, based on pooled SMD, showed decreased muscle activity, lower postural control and balance indices, lower kinematic and kinetic parameters and reach distance in patients with CAI. In the most of the parameters, copers and healthy subjects were considered similar. The findings meta-analysis revealed that patients with CAI demonstrated more neuromuscular deficits than the other groups. Theses deficits provide opportunities for better intervention and prevention strategy after ankle sprain.